Influence of transverse rebar on shear behavior of Y-type perfobond rib shear connection. (20th August 2018) - Kim, Sang-Hyo; Kim, Kun-Soo; Han, Oneil; Park, Jun-Seung
Highlights: Behavior of Y-type perfobond rib shear connections with various strength and diameter of transverse rebar were evaluated. Push-out tests were conducted to evaluate the shear resistance and ductility of Y-type perfobond rib shear connections. Push-out test results were compared with predicted results by existing models. Failure modes of Y-type perfobond rib shear connections were classified into three types. Abstract: This study experimentally investigated the effects of transverse rebar on the shear behavior of Y-type perfobond rib shear connectors. Push-out tests were performed on 12 specimens for which the strength and diameter of transverse rebar were utilized as variables. Test results from a previous study were used to confirm the shear strength and ductility of the Y-type perfobond rib shear connectors, along with the initial cracking and failure modes of the concrete. The results showed that shear strength increased as the diameter of the transverse rebar increased, and this effect was amplified in concrete with lower compressive strength.